2017
DOI: 10.3389/fpls.2017.02206
|View full text |Cite
|
Sign up to set email alerts
|

The Ratio between Field Attractive and Background Volatiles Encodes Host-Plant Recognition in a Specialist Moth

Abstract: Volatiles emitted by plants convey an array of information through different trophic levels. Animals such as host-seeking herbivores encounter plumes with filaments from both host and non-host plants. While studies showed a behavioral effect of non-host plants on herbivore host location, less information is available on how a searching insect herbivore perceives and flies upwind to a host-plant odor plume within a background of non-host volatiles. We hypothesized here that herbivorous insects in search of a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Previous studies showed attraction of both sexes of L. botrana to volatiles emitted by host plants, including grapevine Vitis vinifera and flax-leaved daphne Daphne gnidium [11][12][13] . Although promising, these laboratory and semi-field results were not mirrored by trap catches in the field, due possibly to a suboptimal release of single compounds and blend ratios from dispensers, suboptimal trap properties, and the competition with the background volatiles emitted by the crop 14 .…”
mentioning
confidence: 91%
“…Previous studies showed attraction of both sexes of L. botrana to volatiles emitted by host plants, including grapevine Vitis vinifera and flax-leaved daphne Daphne gnidium [11][12][13] . Although promising, these laboratory and semi-field results were not mirrored by trap catches in the field, due possibly to a suboptimal release of single compounds and blend ratios from dispensers, suboptimal trap properties, and the competition with the background volatiles emitted by the crop 14 .…”
mentioning
confidence: 91%
“…In the present field studies we aimed to (1) improve the effectiveness of existing monitoring insect traps in strawberry and raspberry by increasing catches of both sexes of the three target species, and (2) to demonstrate that two unrelated pest species could be attracted by semiochemicals to the same trap without decreasing the total catches. The possible influence of background volatiles on trapping success (Cai et al, 2017;Knudsen et al, 2017), made it preferable to carry out experiments in the field rather than the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…P-anisaldehyde is a common plant volatile (Knudsen et al 2006 ) that is known to be a semiochemical signal for a number of arthropod species (El-Sayed 2019 ; Morgan and Crumb 1928 ). For example, p-anisaldehyde has been found to be attractive to several species of thrips (Thysanoptera: Thriphidae) (Hollister et al 1995 ; Kirk 1985 ; Koschier et al 2000 ) and the apple fruit moth Argyresthia conjugella Zeller (Lepidoptera: Argyresthiidae) (Bengtsson et al 2006 ; Knudsen et al 2017 ). Also, in the varied carpet beetle Anthrenus verbasci L. (Coleoptera: Dermestidae), p-anisaldehyde has been reported to be a potent attractant for both sexes, and for males is nearly as attractive as the female sex pheromone (Imai et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%